Anti-CD38 autoantibodies in type? diabetes - Mallone, Roberto (John Wiley & Sons, Ltd., 2006)
Human diabetes mellitus comprises two main clinical entities: type 1 and type 2 diabetes. While type 1 diabetes is autoimmune in origin, type 2 diabetes is due to a decreased sensitivity to insulin action (so called insulin resistance) associated to impaired beta cell function. However, it is becoming increasingly clear that there is a certain overlap between these two diseases. While some degree of insulin resistance is present in type 1 patients, markers of beta cell autoimmunity (either primary or secondary) can frequently be detected in type 2 subjects. In this scenario, anti-CD38 autoantibodies (aAbs) have been described in both type 1 and type 2 diabetic patients. Contrary to the other known islet aAbs, anti-CD38 are more prevalent in long-standing than in new onset type 1 diabetes, and more prevalent in type 2 than in type 1 disease. Moreover, anti-CD38 aAbs are endowed with unique stimulatory properties on Ca(2+) mobilization and insulin secretion. These observations suggest that autoimmunity may be both cause and consequence of beta cell dysfunction, in either case imposing a further toll for the control of glucose homeostasis.